Experimental investigation of the influence of ethanol and biodiesel on common rail direct injection diesel Engine's combustion and emission characteristics. (November 2022) - Wai, Phyo; Kanokkhanarat, Phobkrit; Oh, Ban-Seok; Wongpattharaworakul, Veerayut; Depaiwa, Nattawoot; Po-ngaen, Watcharin; Chollacoop, Nuwong; Srisurangkul, Chadchai; Kosaka, Hidenori; Yamakita, Masaki; Charoenphonphanich, Chinda; Karin, Preechar
Abstract: This study aims to characterize the effect of oxygenated biofuels in diesel engine combustion, thermal efficiency, and emission by blending different percentages of ethanol and biodiesel with fossil fuel derived diesel. In this research, 5% and 10% by weight of bioethanol were added to commercial B10 (10% biodiesel and 90% diesel), B20 (20% biodiesel and 80% diesel) and B100 (100% biodiesel) and experimented on using a 3 L four-cylinder common rail diesel engine. The experiment was performed under three engine speeds of 1000 rpm, 1500 rpm, and 2000 rpm with three constant engine torques of 56 Nm, 84 Nm, and 140 Nm. The results show that ethanol-biodiesel-diesel ternary blended fuels are higher in premixed combustion pressure and net heat release rate (NHRR) peaks. The cumulative heat release of ethanol blended fuels is also higher for ethanol blended fuels. The fuel consumption increased with the ethanol and biodiesel percentage in the blended fuels due to the lower heating value while the brake thermal efficiency did not decrease. It was clearly observed that the particle emission could be reduced by more than 50% when ethanol and biodiesel percentage increased.